2011
DOI: 10.1007/s11071-011-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis and control of a new hyperchaotic finance system

Abstract: In this paper, a new hyperchaotic finance system which is constructed based on a chaotic finance system by adding an additional state variable is presented. The basic dynamical behaviors of this hyperchaotic finance system are investigated, such as the equilibrium, stability, hyperchaotic attractor, Lyapunov exponents, and bifurcation analysis. Furthermore, effective speed feedback controllers and linear feedback controllers are designed for stabilizing hyperchaos to unstable equilibrium points. Numerical simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
152
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 15 publications
(17 reference statements)
0
152
0
Order By: Relevance
“…In this section, some preliminaries including the novel hyperchaotic system model ( [28]), some necessary definitions and lemmas are presented, which are used throughout this paper.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, some preliminaries including the novel hyperchaotic system model ( [28]), some necessary definitions and lemmas are presented, which are used throughout this paper.…”
Section: Preliminariesmentioning
confidence: 99%
“…Let ε 1 = 1. In ( [28]) typical phase portraits of this system are shown. It is also shown that in hyperchaotic region of parameters, this system is a forced dissipative system with bounded states (M ≤ 4) as t → ∞.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, more and more scholars improve it by adding an additional state variable [4,5]. Recently, a novel financial hyperchaotic system was brought up [6] on the ground of global economic crisis arousing from 2007. The dynamical behaviors of the new system are more complex.…”
Section: Introductionmentioning
confidence: 99%